"Out of place" in the postwar city: experiences and representations of displacement during the resettlement of Leningrad at the end of the blockade - Peeling, S. Siobahn (2010)
This thesis explores the repopulation of Leningrad following the blockade of the city during the Second World War. In the years after the lifting of the siege blockade survivors remaining in Leningrad were joined annually by hundreds of thousands of incomers. However, while the siege has recently been the subject of a number of scholarly and literary treatments, much less attention has been paid to what happened next in terms of the mass resettlement of the city. Accounts of the consequences of the blockade that touch upon the postwar population have deployed the term ‘Leningraders’ as shorthand for a cohesive community of blockade survivors, embedded in the culture and landscape of the city. Even pieces of work that have portrayed post-siege Leningrad as a ‘city of migrants’ have concentrated on the impact of the loss of the prewar population rather than on the multifarious experiences of its itinerant populations.